Cross‐border migration and initiation of others into drug injecting in Tijuana, Mexico. (22nd November 2017) - Rafful, Claudia; Melo, Jason; Medina‐Mora, María Elena; Rangel, Gudelia; Sun, Xiaoying; Jain, Sonia; Werb, Dan
Abstract: Introduction and Aims: Efforts to prevent injection drug use (IDU) are increasingly focusing on the role that people who inject drugs (PWID) play in facilitating the entry of others into this behaviour. This is particularly relevant in settings experiencing high levels of IDU, such as Mexico's northern border region, where cross‐border migration, particularly through forced deportation, has been found to increase a range of health and social harms related to injecting. Design and Methods: PWID enrolled in a prospective cohort study in Tijuana, Mexico, since 2011 were interviewed semi‐annually, which solicited responses on their experiences initiating others into injecting. Univariate and multivariable logistic regression analyses were conducted at the Preventing Injection by Modifying Existing Responses (PRIMER) baseline, with the dependent variable defined as reporting ever initiating others into injection. The primary independent variable was lifetime deportation from the USA to Mexico. Results: Among 532 participants, 14% ( n = 76) reported initiating others into injecting, the majority of participants reporting initiating acquaintances (74%, n = 56). In multivariable analyses, initiating others into injecting was independently associated with reporting living in the USA for 1–5 years [adjusted odds ratio (AOR) = 2.42; 95% confidence interval (CI) 1.22–4.79, P = 0.01], and methamphetamine and heroin injection combined (AOR = 3.67; 95% CI 1.11–12.17, P = 0.03). Deportation was not independently associated with initiating others into injecting. Discussion and Conclusions: The impact of migration needs to be considered within binational programming seeking to prevent the expansion of epidemics of injecting and HIV transmission among mobile populations residing in the Mexico–USA border region.